Hepatocyte-targeting gene transfer mediated by galactosylated poly(ethylene glycol)- graft-polyethylenimine derivative - Wang YQ; Su J; Cai WW; Lu P; Yuan LF; Jin T; Chen SY; Sheng J (Dove Medical Press, 2013)
Yuqiang Wang,1,* Jing Su,2,* Wenwei Cai,3 Ping Lu,3 Lifen Yuan,3 Tuo Jin,2 Shuyan Chen,1 Jing Sheng3 1Department of Geriatrics, Xinhua Hospital Affiliated to Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 2School of Pharmacy, Shanghai Jiao Tong University, Shanghai, People’s Republic of China; 3Department of Geriatrics, Shanghai Ninth People’s Hospital Affiliated to Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China *Both authors contributed equally to this work Abstract: Biscarbamate cross-linked polyethylenimine derivative (PEI-Et) has been reported as a novel nonviral vector for efficient and safe gene transfer in our previous work. However, it had no cell-specificity. To achieve specific delivery of genes to hepatocytes, galactosylated poly(ethylene glycol)-graft-polyethylenimine derivative (GPE) was prepared through modification of PEI-Et with poly(ethylene glycol) and lactobionic acid, bearing a galactose group as a hepatocyte-targeting moiety. The composition of GPE was characterized by proton nuclear magnetic resonance. The weight-average molecular weight of GPE measured with a gel permeation chromatography instrument was 9489 Da, with a polydispersity of 1.44. GPE could effectively condense plasmid DNA (pDNA) into nanoparticles. Gel retardation assay showed that GPE/pDNA complexes were completely formed at weigh ratios (w/w) over 3. The particle size of GPE/pDNA complexes was 79–100 nm and zeta potential was 6–15 mV, values which were appropriate for cellular uptake. The morphology of GPE/pDNA complexes under atomic force microscopy appeared spherical and uniform in size, with diameters of 53–65 nm. GPE displayed much higher transfection efficiency than commercially available PEI 25 kDa in BRL-3A cell lines. Importantly, GPE showed good hepatocyte specificity. Also, the polymer exhibited significantly lower cytotoxicity compared to PEI 25 kDa at the same concentration or weight ratio in BRL-3A cell lines. To sum up, our results indicated that GPE might carry great potential in safe and efficient hepatocyte-targeting gene delivery. Keywords: gene delivery, hepatocyte targeting, galactose, cytotoxicity, transfection efficiency